pVAXhsp65 Vaccination Primes for High IL-10 Production and Decreases Experimental Encephalomyelitis Severity - Sofia Fernanda Gonçalves Zorzella-Pezavento; Fernanda Chiuso-Minicucci; Thais Graziela Donegá França; Larissa Lumi Watanabe Ishikawa; Larissa Camargo da Rosa; Priscila Maria Colavite; Bianca Balbino; Camila Marques; Maura Rosane Valerio Ikoma; Ana Paula Masson; Célio Lopes Silva; Alexandrina Sartori (Journal of Immunology Research)
Experimental autoimmune encephalomyelitis (EAE) is a demyelinating pathology of the central nervous system (CNS) used as a model to study multiple sclerosis immunopathology. EAE has also been extensively employed to evaluate potentially therapeutic schemes. Considering the presence of an immune response directed to heat shock proteins (hsps) in autoimmune diseases and the immunoregulatory potential of these molecules, we evaluated the effect of a previous immunization with a genetic vaccine containing the mycobacterial hsp65 gene on EAE development. C57BL/6 mice were immunized with 4 pVAXhsp65 doses and 14 days later were submitted to EAE induction by immunization with myelin oligodendrocyte glycoprotein (MOG35–55) emulsified in Complete Freund’s Adjuvant. Vaccinated mice presented significant lower clinical scores and lost less body weight. MOG35–55 immunization also determined less inflammation in lumbar spinal cord but did not change CD4+CD25+Foxp3+ T cells frequency in spleen and CNS. Infiltrating cells from the CNS stimulated with rhsp65 produced significantly higher levels of IL-10. These results suggest that the ability of pVAXhsp65 vaccination to control EAE development is associated with IL-10 induction.